The Nature of Material Reality: Interreligious Conversations at the Cusp of Modern Science in India - Christian, Charles (Philosophy, theology and the sciences, 2022)
text of India in a certain way. However, we also argue that the interreligious conversation between both the interlocutors disclose that they held their views not as mere constructions under contextual pressures, but as alternative perspectives on the same reality and that they held these perspectives with 'universal intent.' Discerning a certain dialectic relationship between contextual and universal factors can help to both understand the nature of interreligious dialogue and recognise its relevance for global discourse on science and religion.